Between Religion and Religiosity: Between the Death and Resurrection of God - Avi Sagi (Religions)
The main thesis presented in this article rejects the identification of the “death of God” idea with atheism. Atheism is a metaphysical claim stating that the signifier God has no signified. By contrast, the “death of God” notion conveys a moment of crisis in believers’ lives where the God that had been present in their lives is dead. The “death of God” idea led, on the one hand, to the negation of God’s relevance in human life, as presented by Nietzsche, and, on the other, to its perception as a constitutive moment for religion itself due to God’s presence in the believer’s inner life, as outlined by Kierkegaard, Simone Weil, and others. Both approaches agree on the crucial role of religiosity, whether or not it has a transcendent object. This analysis challenges the dichotomy claiming that, on the one hand, believers cannot accept the idea of the death of God and, on the other hand, those who endorse the death of God negate the idea of religiosity.